Plate Removal after Internal Fixation of Limb Fractures: A Retrospective Study of Indications and Complications in 48 Horses - Donati, Brice; Fürst, Anton E.; Del Chicca, Francesca; Jackson, Michelle A. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to determine the indications for, and complications of, plate removal surgery in horses that underwent internal fixation of limb fractures.Study Design Medical records of horses presented to our hospital between 1990 and 2015 for the removal of plates after treatment of limb fractures were reviewed. Data collected at the time of initial presentation, including signalment, history, fracture features and treatment and information about the indications, timing and complications of implant removal were reviewed.Results The most common bones involved were the ulna (n = 19) and third metacarpal and metatarsal bones (n = 14). A total of 63 plates were removed from 48 horses during 53 separate surgeries, and the complication rate was 6/48; six horses had complications related to implant removal, which included persistent infection (n = 1) and refracture (n = 5). Complications related to implant removal were associated with comminuted fractures (p = 0.002), age > 3 years (p = 0.016) and the presence of surgical site infection (p = 0.001).Conclusion Plate removal after fracture healing is necessary in patients with implant-associated clinical signs. There is a strong relationship between the complication rate and the degree of comminution of the original fracture, increasing age and the presence of surgical site infection. The surgeon must be aware of these risk factors when planning plate removal.
Keywords: horse; osteosynthesis; plate removal; complications; refracture